The Effectiveness of Peppermint Aromatherapy for Nausea and Vomiting in Pregnant Women in the First Trimester - Shinta Ayu Retnawati; Yeti Trisnawati (Althar Cendikia Education, 2026)
Nausea and vomiting (emesis gravidarum) are common symptoms during the first trimester of pregnancy due to hormonal changes, particularly increased levels of human chorionic gonadotropin (hCG), estrogen, and progesterone. These symptoms may interfere with daily activities, reduce nutritional intake, and impair maternal quality of life. Peppermint aromatherapy, which contains menthol with antiemetic and relaxing properties, is a potential non-pharmacological intervention. This study aimed to evaluate the effect of peppermint aromatherapy on nausea and vomiting among first-trimester pregnant women. A quasi-experimental pretest–posttest control group design was employed involving 30 participants, equally assigned to intervention and control groups. Nausea and vomiting were assessed before and after the intervention using a standardized measurement scale. Data were analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test. The intervention group showed a significant reduction in mean nausea and vomiting scores from 2.13 to 1.07 (p = 0.001), whereas the control group showed no significant change (2.07 to 1.93; p = 0.414). A significant difference was also observed between groups (Z = −3.089; p = 0.002). Peppermint aromatherapy effectively reduced nausea and vomiting in first-trimester pregnant women and may serve as a safe complementary therapy.